Diseases of the retina and the optic nerve associated with obstructive sleep apnea. (April 2018) - Mentek, Marielle; Aptel, Florent; Godin-Ribuot, Diane; Tamisier, Renaud; Pepin, Jean-Louis; Chiquet, Christophe
Summary: Many associations between ocular disorders and obstructive sleep apnea (OSA) have been studied, such as nonarteritic anterior ischemic optic neuropathy, glaucoma, papilledema, retinal vein occlusion, eyelid hyperlaxity, lower-eyelid ectropion and recurrent corneal erosions. The objective of this review is to synthetize the possible vascular disorders of the retina and the optic nerve associated with sleep apnea patients and to discuss the underlying pathophysiological hypotheses. Main mechanisms involved in the ocular complications of OSA are related to intermittent hypoxia, sympathetic system activation, oxidant stress, and deleterious effects of endothelin 1. The main evidence-based medicine data suggest that OSA should be screened in patients with ischemic optic neuropathy and diabetic retinopathy. The effect of OSA treatment and emerging therapies are discussed.